Exploring the In vitro Antibacterial Efficacy of Yemidir Embuay (Cucumis focifolius) and Endod (Phytolacca dodecandra) of Different Extracts Against Some Bacteria Pathogens - Wanore, Denebo Sebaro; Fantu , Henok Mesfin; Degu, Elsabeth Estifanos; Lelisho , Dilame Lemma; Badulo, Tesfaye Lamore; Futase, Tiringo Markos (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Medicinal plants are one of the most indigenous resources in the world for the treatment of different diseases. Now a day most of infectious diseases are resistant to the antimicrobial agents. Therefore, the aim of this study was to explore the efficacy of Cucumis focifolius and Phytolacca dodecandra against Staphylococcus aureus, Klebsiella Pneumonia and Neisseria gonorrhea. Ethanol, Methanol, Chloroform and Water are used as solvents for the extraction of phytochemical compounds from Cucumis focifolius and Phytolacca dodecandra plants. The effective extraction of bioactive compounds was achieved using methanol, chloroform and water as solvents. According to this study there were bioactive compounds that extracted from selected plants which were potentially effective against Neisseria gonorrhea and some other pathogens. Both Cucumis focifolius and Phytolacca dodecandra some inhibition zone on S. auerus and k. pneumonia strains. Highly statistical significant antibacterial effect against N. gonorrhea (16.6±3.05) for ethanol root extract of Cucumis focifolius followed by methanol root extract with an inhibition zone of (15±2.64) were exhibited. The extract also shows (13.3±1.25mm, 14±1.05mm by chloroform and distilled water root extract respectively. Ethanol C. focifolius root shows lowest Minimum inhibitory concentration against Neisseria gonorrhea as compared to other extracts. Therefore, we recommend people to search for new antimicrobial agents for better treatment of Neisseria Gonorrhea, which is one of causative agent of sexual transmitted disease.